An evaluation of the 'Designated Research Team' approach to building research capacity in primary care - Dyas Jane (BMC Family Practice, 2008)
Abstract Background This paper describes an evaluation of an initiative to increase the research capability of clinical groups in primary and community care settings in a region of the United Kingdom. The 'designated research team' (DRT) approach was evaluated using indicators derived from a framework of six principles for research capacity building (RCB) which include: building skills and confidence, relevance to practice, dissemination, linkages and collaborations, sustainability and infrastructure development. Methods Information was collated on the context, activities, experiences, outputs and impacts of six clinical research teams supported by Trent Research Development Support Unit (RDSU) as DRTs. Process and outcome data from each of the teams was used to evaluate the extent to which the DRT approach was effective in building research capacity in each of the six principles (as evidenced by twenty possible indicators of research capacity development). Results The DRT approach was found to be well aligned to the principles of RCB and generally effective in developing research capabilities. It proved particularly effective in developing linkages, collaborations and skills. Where research capacity was slow to develop, this was reflected in poor alignment between the principles of RCB and the characteristics of the team, their activities or environment. One team was unable to develop a research project and the funding was withdrawn at an early stage. For at least one individual in each of the remaining five teams, research activity was sustained beyond the funding period through research partnerships and funding successes. An enabling infrastructure, including being freed from clinical duties to undertake research, and support from senior management were found to be important determinants of successful DRT development. Research questions of DRTs were derived from practice issues and several projects generated outputs with potential to change daily practice, including the use of research evidence in practice and in planning service changes. Conclusion The DRT approach was effective at RCB in teams situated in a supportive organisation and in particular, where team members could be freed from clinical duties and management backing was strong. The developmental stage of the team and the research experience of constituent members also appeared to influence success. The six principles of RCB were shown to be useful as a framework for both developing and evaluating RCB initiatives.